Analisis Kesulitan Mahasiswa PPL Pendidikan Geografi dalam Mengimplementasikan Kurikulum Merdeka - Rahmayati, Sri Dila; Afdhal, Afdhal (ALSYS, 2024)
Field Experience Practice Activities for Geography Education students in the July-December 2023 period were carried out in the second year of implementing the Independent Curriculum in a number of schools in Bukittinggi City. This research aims to analyze the difficulties experienced by Geography Education students for the July-December 2023 period in implementing the Independent Curriculum in State High Schools and State Islamic high School in Bukittinggi City. The research method used is qualitative research with a phenomenological approach. The results of this research show that the difficulties experienced by Geography Education students occurred in the planning, implementation and assessment of the learning process. Difficulties experienced by students are influenced by factors from within the student as well as factors from outside the student, originating from the students, the environment and learning support facilities.